Representasi Peran Wanita pada Buku Teks Pembelajaran Sejarah Indonesia Kelas XI SMA - Wina Puspita Sari; Andi, Andi (Universitas Hamzanwadi, 2024)
This abstract describes the representation of the role of women in the historical learning textbooks of the eleventh grade edition of Erlangga, Kemendikbud, and Quadra. The study aims to enable students to understand and learn about the role of women heroes who have fought for their people in textbooks. As well as improving gender equality and tolerance of diversity within the pupils. The research uses qualitative methods with content analysis approaches and verifies the validity of data through triangulation of sources and methods. Data obtained from interviews, document studies, learning observations, and analysis of class XI history textbooks issued by Erlangga, Kemendikbud, and Quadra. The textbooks Erlangga, Kemendikbud, and Quadra do not fully cover the role of female heroes, thus raising the stereotype that only men play an important role in the fight against the invaders. This lack of representation ignores the contribution of women to history and strengthens gender bias among pupils.